Introduction and scientific justification of data transportability for confined field testing for the ERA of GM plants - Nakai, Shuichi; Roberts, Andrew F.; Simmons, Abigail R.; Hiratsuka, Kazuyuki; Miano, Douglas W.; Vesprini, Facundo (Frontiers in Bioengineering and Biotechnology, 2024)
The concept of Data Transportability (DT) of Confined Field Testing (CFT) to support the Environmental Risk Assessment (ERA) of Genetically Modified (GM) plants was first introduced in the literature by Garcia-Alonso et al. in 2014. Since then, DT has been discussed in many countries and regions as a concept to prevent duplication of regulatory studies without compromising quality of the ERA. However, despite its usefulness and scientific justification, DT is not well adopted at this time and many regulatory agencies around the world require an additional in-country CFT be conducted before approving GM plants. Based on the current circumstances, the authors organized a parallel session entitled “Introduction & Scientific Justification of DT for CFT for the ERA of GM plants” at 16th ISBR (the International Society for Biosafety Research). This session mainly consisted of the following three parts. The first two speakers, Andrew Roberts and Abigail Simmons provided an overview of DT and examples of conditions for the transportability of field data/conclusions advocated in the peer-reviewed scientific journals. Next, the current status of DT adoption in some countries/regions such as Japan and Africa, and a theoretical case study for Argentina were introduced by Kazuyuki Hiratsuka, Douglas Miano and Facundo Vesprini, respectively. Lastly, a risk hypothesis-based approach for DT which was developed in advance by the five speakers of this parallel session, was introduced. During the discussion, there was a common understanding that transition to the risk hypothesis-based approach for DT was scientifically appropriate, considering the accumulated evidences that several countries have conducted confirmatory local CFT for more than 20 years but they have not detected any differences related to the ERA assessment endpoints in GM crops. The risk hypothesis-based approach for DT introduced here is expected to play an important role in discussions on the implementation of DT in various parts of the world in the future.